The Concept of Sufism in Surah Al-A‘la Verses 14–15 in the Book Tafsir Lath?’if al-Ish?r?t by Imam Al-Qushayri: (An Analysis Using Fazlur Rahman’s Double Movement Theory) - Kamal Haddad; Ahmad Zohdi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
ABSTRACT This study aims to examine the concept of Sufism according to Imam al-Qushayri in his interpretation of Surah al-A‘l? verses 14–15 as presented in the book Lath?’if al-Ish?r?t. This research employs a qualitative approach using a library research method, through a tahlili analysis of the Qur’anic verses and al-Qushayri’s interpretation, supported by Fazlur Rahman’s Double Movement theory to assess the relevance of the findings in a contemporary context. The results show that al-Qushayri interprets these verses using an ish?r?-sunni approach, namely a Sufi interpretation that remains grounded in the outward (??hir) meaning of the verses before exploring their inner (b??in) dimensions. In the phrase “qad aflaha man tazakk?” (“Indeed, successful is the one who purifies himself”), Imam al-Qushayri emphasizes that spiritual success can only be attained through the purification of the heart from reprehensible traits, the control of desires, and the strengthening of moral character as the foundation of inner purity. Meanwhile, in the phrase “wa dhakara isma rabbih? fa?all?” (“and mentions the name of his Lord and prays”), he asserts that remembrance (dhikr) is the core of a servant’s spiritual life and serves as the gateway to inner ???? (presence) in worship, particularly in prayer, which is understood as a meeting of the heart with Allah. Through the Double Movement theory, this study finds that the moral message of al-Qushayri’s interpretation is universal and relevant to modern life. The first movement indicates that, during the time of the Prophet, these verses emphasized the development of moral character, purification of the soul, and the spiritual steadfastness of the companions. The second movement demonstrates that these values can be actualized in contemporary life as ethical foundations for character building, as spiritual therapy for modern anxieties, and as a reinforcement of divine consciousness in daily activities. Keywords: Sufism, Imam al-Qushayri, Lath?’if al-Ish?r?t, Fazlur Rahman’s Double Movement.